2021
DOI: 10.1021/acs.jnatprod.0c01065
|View full text |Cite
|
Sign up to set email alerts
|

In Planta Discovery and Chemical Synthesis of Bracelet Cystine Knot Peptides from Rinorea bengalensis

Abstract: Cyclotides are plant-derived peptides that have attracted interest as biocides and scaffolds for the development of stable peptide therapeutics. Cyclotides are characterized by their cyclic backbone and cystine knot framework, which engenders them with remarkably high stability. This study reports the cystine knotrelated peptidome of Rinorea bengalensis, a small rainforest tree in the Violaceae family that is distributed from Australia westward to India. Surprisingly, many more acyclic knotted peptides (acyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…cyclotide related peptides that do not contain a cyclic backbone, which have been referred to as acyclotides) [ 17 ]. In contrast, analysis of another Violaceae plant species, Rinorea bengalensis , showed a large number of acyclotides and only one cyclotide sequence [ 18 ]. Despite the lack of the cyclic backbone, several of these peptides have been shown to have cytotoxic activities similar to their cyclic counterparts [ 18 ].…”
Section: Discovery and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…cyclotide related peptides that do not contain a cyclic backbone, which have been referred to as acyclotides) [ 17 ]. In contrast, analysis of another Violaceae plant species, Rinorea bengalensis , showed a large number of acyclotides and only one cyclotide sequence [ 18 ]. Despite the lack of the cyclic backbone, several of these peptides have been shown to have cytotoxic activities similar to their cyclic counterparts [ 18 ].…”
Section: Discovery and Characterisationmentioning
confidence: 99%
“…In contrast, analysis of another Violaceae plant species, Rinorea bengalensis , showed a large number of acyclotides and only one cyclotide sequence [ 18 ]. Despite the lack of the cyclic backbone, several of these peptides have been shown to have cytotoxic activities similar to their cyclic counterparts [ 18 ]. New cyclotide sequences have also recently been found in Palicourea sessilis , that have potential as immunosuppressants [ 19 ].…”
Section: Discovery and Characterisationmentioning
confidence: 99%
“…Acyclotides have a similar sequence to cyclotides and also contain a cystine knot, but lack a head-to-tail cyclic backbone. The backbone cyclization is absent due to a stop codon occupying the position that would encode an Asx (Asn or Asp) residue in a typical cyclotide precursor (20). This key Asx residue and an adjacent C-terminal tail peptide in the precursor facilitates cyclization in cyclotides by asparaginyl endopeptidase (AEP) enzymes in plants (19,21).…”
Section: Introductionmentioning
confidence: 99%
“…This key Asx residue and an adjacent C-terminal tail peptide in the precursor facilitates cyclization in cyclotides by asparaginyl endopeptidase (AEP) enzymes in plants (19,21). Despite their acyclic backbone, acyclotides have comparable stability and structures to cyclotides, primarily due to the stabilizing effect of the cystine knot motif (20,22). Apart from local changes at the terminal residues, the NMR structures of two acyclotides, violacin A and MCoTI-V, have shown that linearization has negligible effects upon the structure of the cystine knot core (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation